Polymorphisms in Dopaminergic Genes in Schizophrenia and Their Implications in Motor Deficits and Antipsychotic Treatment - Ye, Jiaen; Ji, Feng; Jiang, Deguo; Lin, Xiaodong; Chen, Guangdong; Zhang, Wei; Shan, Peiwei; Zhang, Li; Zhuo, Chuanjun (Frontiers in Neuroscience, 2019)
Dopaminergic system dysfunction is involved in schizophrenia (SCZ) pathogenesis and can mediate SCZ-related motor disorders. Recent studies have gradually revealed that SCZ susceptibility and the associated motor symptoms can be mediated by genetic factors, including dopaminergic genes. More importantly, polymorphisms in these genes are associated with both antipsychotic drug sensitivity and adverse effects. The study of genetic polymorphisms in the dopaminergic system may help to optimize individualized drug strategies for SCZ patients. This review summarizes the current progress about the involvement of the dopamine system in SCZ-associated motor disorders and the motor-related adverse effects after antipsychotic treatment, with a special focus on polymorphisms in dopaminergic genes. We hypothesize that the genetic profile of the dopaminergic system mediates both SCZ-associated motor deficits associated and antipsychotic drug-related adverse effects. The study of dopaminergic gene polymorphisms may help to predict drug efficacy and decrease adverse effects, thereby optimizing treatment strategies.